Penentuan Senyawa Dan Pemodelan Suhu Pada Saat Pemanasan Batu Kapur Untuk Mendapatkan CaO Murni Dari Batu Kapur Papua - Egosrivajawaty Sinaga; Hubertus Ngaderman (LPPM Universitas Muhammadiyah Riau, 2020)
ABSTRACT Determination of compounds and temperature modeling during heating of limestone have been carried out to obtain pure CaO from Papua limestone. . The purpose of this research is to determine the compounds, morphology and characteristics of each element and molecule present in limestone from Papua and to simply model the optimum temperature to obtain CaO. From the results of XRF testing, there is one main element that contains the most chemical elements in the limestone sample from black soil (sample 1) and perumnas three (sample 2), namely Ca (calcium) with weight percent 99.57 and 99.69. XRD results are also supported from characterization with EDS where the dominant elements of sample 1 are O, Ca and Mg in sample 2 dominant elements Ca, O and C. Then based on SEM analysis, the morphology of CaMg (CO3) 2, Ca (Co3) and MgCa ( Co3) resembles a cube but the particle size is uneven and irregular due to impurities. The temperature obtained based on the results of this calculation is 12800C.